Composite positive electrode material for lithium ion battery and preparation method of composite positive electrode material
By introducing lithium supplementary materials and catalytic materials into the positive electrode materials of lithium-ion batteries, the structural changes and safety problems of lithium-ion batteries during the circulation process are solved, and higher cycle stability and safety are achieved.
Patent Information
- Application Number
- CN202411450747.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-17
AI Technical Summary
There are structural changes and the precipitation of transition metal ions during the circulation process of high-energy density lithium-ion batteries, which lead to the rupture, decomposition and fall off of materials, reducing the cycle life and safety of the battery.
Using composite positive electrode materials, including positive electrode matrix material, lithium supplement material and catalytic material, the lithium supplement material is coated on the outside of the positive electrode matrix material through in-situ preparation, and catalytic material is introduced on the surface of the lithium supplement material to fix free oxygen and stabilize the structure.
It improves the cycle stability and safety of lithium-ion batteries, extends the service life of the battery, reduces production costs, adapts to existing processes, and is easy to promote.
Smart Images

Figure CN119517954A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite positive electrode material for lithium ion batteries and a preparation method thereof. Background Art
[0002] With the rapid development of personal consumer electronics and electric vehicles, higher requirements are put forward for lithium-ion batteries to achieve longer standby time and driving range: high energy density, long cycle life, and good safety. In order to improve the energy density of the battery, high-gram capacity positive and negative electrode materials are generally used. During the cycle process, high-gram capacity positive electrode materials are usually accompanied by changes in crystal structure and precipitation of transition metal ions, causing the material particles to break, decompose, and fall off, resulting in rapid attenuation of material capacity. The positive electrode material is usually surface modified to inhibit the occurrence of irreversible changes, improve the structural stability of the material, and thus improve the cycle life and safety of the battery. At present, high-energy-density lithium-ion batteries mostly use silicon-based negative electrode materials, but during the charge and discharge of silicon-based negative electrodes, due to the formation of SEI film, the first irreversible capacity is more than 20%, which seriously reduces the energy density of the battery. Therefore, researchers use lithium supplementation technology to compensate for the lithium loss in the first charging process and improve the energy density and cycle life of lithium-ion batteries.
[0003] Surface modification of positive electrode materials is usually achieved by ion doping and surface coating. Lithium replenishment technology is divided into negative electrode replenishment and positive electrode replenishment. Negative electrode lithium replenishment materials are extremely unstable in the air, and the lithium replenishment technology is complex and has strict environmental requirements. It requires major changes to existing production lines and is difficult to promote and apply in the short term. Positive electrode lithium replenishment materials are mostly lithium-rich compounds, which are relatively stable, and the lithium replenishment technology is simple. It does not change the existing battery preparation process much and is easier to implement. Commonly used positive electrode lithium replenishers are mostly lithium-rich materials. + At the same time as it escapes, free O is precipitated, causing the battery bag to swell, leading to a decrease in battery capacity and a series of safety issues.
[0004] Therefore, it is necessary to develop a composite positive electrode material for lithium-ion batteries to overcome the above technical problems. Summary of the invention
[0005] The purpose of the present invention is to solve the cycle stability and safety problems of high energy density lithium ion batteries, and to provide a composite positive electrode material for lithium ion batteries and a preparation method thereof. On the one hand, a composite material of a lithium ion battery positive electrode matrix material and a lithium supplement material is prepared in situ, and the lithium supplement material has the dual functions of surface modification of the positive electrode matrix material and negative electrode lithium supplement, which not only stabilizes the structure of the positive electrode material, but also improves the battery's first efficiency and cycle stability; on the other hand, a catalytic material is introduced on the surface of the lithium supplement material to in situ fix the free O generated by the release of Li from the lithium supplement material, alleviate the battery bag swelling phenomenon, and further improve the battery's cycle stability and safety.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] In a first aspect, the present invention provides a composite positive electrode material for a lithium-ion battery, wherein the composite positive electrode material comprises a positive electrode matrix material, a lithium supplement material and a catalytic material;
[0008] The positive electrode matrix material comprises at least one of lithium iron phosphate material, lithium iron manganese phosphate material, lithium cobalt phosphate material, lithium manganate material, lithium nickel manganate material, lithium cobaltate material, lithium nickel cobalt manganate material, lithium nickel cobalt aluminum oxide material, and lithium-rich oxide material;
[0009] The lithium supplement material comprises at least one of a lithium silicate rich material, a lithium ferrite rich material, a lithium niobate rich material, a lithium zirconate rich material, and a lithium nickelate rich material;
[0010] The catalytic material comprises at least one of iron oxide, manganese oxide, cobalt oxide, nickel oxide, iron sulfide, manganese sulfide, cobalt sulfide, nickel sulfide, iron phosphide, manganese phosphide, cobalt phosphide, nickel phosphide, elemental sulfur, elemental phosphorus, graphene, and carbon nanotubes;
[0011] In the composite positive electrode material, the molar proportions of the positive electrode matrix material, the lithium supplement material, and the catalytic material are 80 to 98 parts, 0.01 to 19 parts, and 0.001 to 1 part, respectively;
[0012] The positive electrode matrix material is inside the composite positive electrode material, and the lithium supplement material and the catalytic material are coated on the outside of the positive electrode matrix material.
[0013] Preferably, the particle size of the composite positive electrode material particles is 1 to 20 μm, and the coating thickness of the lithium supplement material and the catalytic material is 1 to 30 nm.
[0014] Preferably, the positive electrode matrix material is a nickel-cobalt-manganese-lithium oxide material, the lithium supplement material is a lithium-rich silicate material, and the catalytic material is a mixture of iron sulfide and iron oxide.
[0015] Preferably, the positive electrode matrix material is a lithium cobalt oxide material, the lithium supplement material is a lithium ferrite-rich material, and the catalytic material is a mixture of phosphorus and cobalt phosphide.
[0016] In a second aspect, the present invention provides a method for preparing the composite positive electrode material for a lithium ion battery according to the first aspect, the specific steps are as follows:
[0017] Preparation of composite materials of S1 positive electrode matrix material and lithium supplement material
[0018] The positive electrode matrix material precursor and the lithium supplement material precursor are mixed evenly in proportion, so that the lithium supplement material precursor is coated on the surface of the positive electrode matrix material precursor; a lithium source is added, and heat-treated at 500-1000° C. to obtain a composite material M1 of the positive electrode matrix material and the lithium supplement material;
[0019] The precursor of the positive electrode matrix material is at least one material selected from the group consisting of iron phosphate, iron manganese phosphate, cobalt phosphate, manganese oxide, nickel manganese oxide, cobalt oxide, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, and lithium-rich oxide; the precursor of the lithium supplement material is at least one material selected from the group consisting of silicon dioxide, iron oxide, niobium oxide, zirconium oxide, and nickel oxide; the lithium source is at least one material selected from the group consisting of lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate;
[0020] The molar ratio of the positive electrode matrix material precursor to the lithium supplement material precursor is 160:1 to 4:1; the molar ratio of the sum of the molar amounts of the positive electrode matrix material precursor + the lithium supplement material precursor to the molar ratio of the lithium source is 1:1.05 to 1.5;
[0021] S2 Preparation of composite cathode materials for lithium-ion batteries
[0022] The prepared composite material M1 and the catalytic material are mixed uniformly in proportion, and subjected to heat treatment at 100-500° C. so that the catalytic material is dispersed on the surface of the composite material M1 and forms a stable interface layer with the lithium supplement material, thereby obtaining a composite positive electrode material for a lithium ion battery;
[0023] The molar ratio of the composite material M1 to the catalytic material is 1:0.001 to 1:1.
[0024] Preferably, the particle size of the positive electrode matrix material precursor is 1-20 μm, the particle size of the lithium supplement material precursor is 0.01-0.2 μm, and the particle size of the catalytic material is 0.01-0.2 μm.
[0025] Preferably, the heat treatment time in step 1 is 1 to 10 hours, and the heat treatment time in step 2 is 1 to 20 hours.
[0026] In a third aspect, the present invention provides a use of the composite positive electrode material described in the first aspect for preparing a lithium ion battery.
[0027] Preferably, the composite positive electrode material is used to prepare a positive electrode of a lithium-ion battery.
[0028] In a fourth aspect, the present invention provides a lithium battery, wherein the positive electrode of the lithium-ion battery is the composite positive electrode material described in the first aspect, and the negative electrode is a carbon silicon material.
[0029] Beneficial effects of the present invention: The method prepares a composite positive electrode material for a lithium-ion battery, which has the following advantages:
[0030] (1) In situ preparation of a composite material of a lithium-ion battery positive electrode matrix material and a lithium supplement material. The lithium supplement material has the dual functions of surface modification of the positive electrode matrix material and negative electrode lithium supplementation, which not only stabilizes the structure of the positive electrode material, but also improves the battery's initial efficiency and cycle stability.
[0031] (2) Synchronously introduce catalytic materials on the surface of the lithium supplement material to in-situ fix the free O generated by the release of Li from the lithium supplement material, alleviate the battery bag swelling phenomenon, and further improve the cycle stability and safety of the battery;
[0032] (3) The prepared composite positive electrode material for lithium-ion batteries has a simple preparation process, low production cost, and is easy to promote industrial production;
[0033] (4) The prepared composite positive electrode material for lithium-ion batteries has good adaptability to the existing lithium-ion battery preparation process, does not require major changes, and is easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Schematic diagram of the structure of composite cathode material
[0035] Among them, 1 represents the positive electrode matrix material, 2 represents the interface layer between the positive electrode matrix material and the lithium supplement material, 3 represents the lithium supplement material coating layer, and 4 represents the surface catalytic material;
[0036] Figure 2 SEM image of the prepared composite cathode material
[0037] Figure 3 200 cycle curves of the battery assembled with the prepared composite cathode material and silicon-carbon material at 0.2C
[0038] In the figure: the ordinate is the discharge capacity, in Ah; the abscissa is the number of cycles, in times. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the accompanying drawings and examples.
[0040] Example 1
[0041] The steps of preparing the composite positive electrode material for lithium-ion batteries are as follows:
[0042] Step 1: Preparation of composite materials of positive electrode matrix material and lithium supplement material
[0043] 0.2 mol of nickel-cobalt-manganese oxide (10 μm) and 0.01 mol of silicon dioxide (0.05 μm) were mixed evenly to allow the silicon dioxide to adhere to the surface of the nickel-cobalt-manganese oxide;
[0044] 0.3 mol of lithium hydroxide was added, mixed evenly, and heat treated at 750° C. for 7 h to obtain a composite material of lithium nickel cobalt manganese oxide and lithium-rich silicate;
[0045] Step 2 Preparation of composite positive electrode materials for lithium-ion batteries
[0046] 0.1 mol of a composite material of lithium nickel cobalt manganese oxide and lithium-rich silicate is evenly mixed with 0.0005 mol of iron sulfide and 0.0005 mol of iron oxide, and heat treated at 300°C for 3 hours to disperse the catalytic material on the surface of the composite material of lithium nickel cobalt manganese oxide and lithium-rich silicate, and form an interface layer with the lithium-rich silicate material, thereby obtaining a composite positive electrode material for lithium-ion batteries.
[0047] The schematic diagram of the prepared material structure is shown in Figure 1 As shown, reference numeral 1 represents the positive electrode matrix material, reference numeral 2 represents the interface layer between the positive electrode matrix material and the lithium supplement material, reference numeral 3 represents the lithium supplement material coating layer coated on the outside of the positive electrode matrix material, and reference numeral 4 represents the surface catalytic material coated on the outside of the lithium supplement material coating layer.
[0048] The SEM image of the prepared composite cathode material is shown in Figure 2 As shown, the particle size of the composite material is 10 μm and is evenly distributed.
[0049] Example 2
[0050] The steps of preparing the composite positive electrode material for lithium-ion batteries are as follows:
[0051] Step 1: Preparation of composite materials of positive electrode matrix material and lithium supplement material
[0052] 0.2 mol of cobalt oxide (2 μm) and 0.01 mol of iron oxide (0.05 μm) were mixed evenly to allow the iron oxide to adhere to the surface of the cobalt oxide;
[0053] 0.3 mol of lithium nitrate was added, mixed evenly, and heat treated at 780°C for 6 hours to obtain a composite material of lithium cobalt oxide and lithium ferrite rich;
[0054] Step 2: Preparation of composite positive electrode materials for lithium-ion batteries
[0055] 0.1 mol of a composite material of lithium cobalt oxide and lithium ferrite-rich is evenly mixed with 0.0006 mol of phosphorus and 0.0004 mol of cobalt phosphide, and heat treated at 120°C for 15 hours to disperse the catalytic material on the surface of the composite material of lithium cobalt oxide and lithium ferrite-rich and form an interface layer with the lithium ferrite-rich material, thereby obtaining a composite positive electrode material for lithium ion batteries.
[0056] The composite positive electrode material prepared in this example was assembled with silicon-carbon material (Bai Te Rui, capacity 600 mAh / g) into a 2.5Ah soft-pack battery. The constant current charge-discharge cycle test was performed at a current density of 0.2C in the voltage range of 2.5 to 4.6 V. The 200 cycle curves are as follows: Figure 3 As shown, it exhibits excellent cycling stability.
Claims
1. A composite positive electrode material for a lithium ion battery, characterized in that: The composite positive electrode material comprises a positive electrode matrix material, a lithium supplement material and a catalytic material; The positive electrode matrix material comprises at least one of lithium iron phosphate material, lithium iron manganese phosphate material, lithium cobalt phosphate material, lithium manganate material, lithium nickel manganate material, lithium cobaltate material, lithium nickel cobalt manganate material, lithium nickel cobalt aluminum oxide material, and lithium-rich oxide material; The lithium supplement material comprises at least one of a lithium silicate rich material, a lithium ferrite rich material, a lithium niobate rich material, a lithium zirconate rich material, and a lithium nickelate rich material; The catalytic material comprises at least one of iron oxide, manganese oxide, cobalt oxide, nickel oxide, iron sulfide, manganese sulfide, cobalt sulfide, nickel sulfide, iron phosphide, manganese phosphide, cobalt phosphide, nickel phosphide, elemental sulfur, elemental phosphorus, graphene, and carbon nanotubes; In the composite positive electrode material, the molar proportions of the positive electrode matrix material, the lithium supplement material, and the catalytic material are 80 to 98 parts, 0.01 to 19 parts, and 0.001 to 1 part, respectively; The positive electrode matrix material is inside the composite positive electrode material, and the lithium supplement material and the catalytic material are coated on the outside of the positive electrode matrix material.
2. The composite positive electrode material for lithium-ion batteries according to claim 1, characterized in that: The particle size of the composite positive electrode material particles is 1 to 20 μm, and the coating thickness of the lithium supplement material and the catalytic material is 1 to 30 nm.
3. The composite positive electrode material for lithium ion battery according to claim 1, characterized in that: The positive electrode matrix material is nickel cobalt manganese oxide material, the lithium supplement material is lithium silicate rich material, and the catalytic material is a mixture of iron sulfide and iron oxide.
4. The composite positive electrode material for lithium ion battery according to claim 1, characterized in that: The positive electrode matrix material is a lithium cobalt oxide material, the lithium supplement material is a lithium ferrite-rich material, and the catalytic material is a mixture of phosphorus and cobalt phosphide.
5. A method for preparing a composite positive electrode material for a lithium ion battery according to any one of claims 1 to 4, characterized in that: The specific steps are as follows: Preparation of composite materials of S1 positive electrode matrix material and lithium supplement material The positive electrode matrix material precursor and the lithium supplement material precursor are mixed evenly in proportion, so that the lithium supplement material precursor is coated on the surface of the positive electrode matrix material precursor; a lithium source is added, and heat-treated at 500-1000° C. to obtain a composite material M1 of the positive electrode matrix material and the lithium supplement material; The precursor of the positive electrode matrix material is at least one material selected from the group consisting of iron phosphate, iron manganese phosphate, cobalt phosphate, manganese oxide, nickel manganese oxide, cobalt oxide, nickel cobalt manganese oxide, nickel cobalt aluminum oxide, and lithium-rich oxide; the precursor of the lithium supplement material is at least one material selected from the group consisting of silicon dioxide, iron oxide, niobium oxide, zirconium oxide, and nickel oxide; the lithium source is at least one material selected from the group consisting of lithium hydroxide, lithium carbonate, lithium acetate, and lithium nitrate; The molar ratio of the positive electrode matrix material precursor to the lithium supplement material precursor is 160:1 to 4:1; the molar ratio of the sum of the molar amounts of the positive electrode matrix material precursor and the lithium supplement material precursor to the molar amount of the lithium source is 1:1.05 to 1:1.5; S2 Preparation of composite cathode materials for lithium-ion batteries The prepared composite material M1 and the catalytic material are uniformly mixed in proportion, and subjected to heat treatment at 100-500° C. to obtain a composite positive electrode material for a lithium-ion battery; The molar ratio of the composite material M1 to the catalytic material is 1:0.001 to 1:
1.
6. The method for preparing a composite positive electrode material for a lithium ion battery according to claim 5, characterized in that: The particle size of the positive electrode matrix material precursor is 1-20 μm, the particle size of the lithium supplement material precursor is 0.01-0.2 μm, and the particle size of the catalytic material is 0.01-0.2 μm.
7. The method for preparing a composite positive electrode material for a lithium ion battery according to claim 5, characterized in that: The heat treatment time in step 1 is 1 to 10 hours, and the heat treatment time in step 2 is 1 to 20 hours.
8. Use of the composite positive electrode material according to any one of claims 1 to 4 in the preparation of lithium ion batteries.
9. The use of the composite positive electrode material for preparing a lithium ion battery according to claim 8, characterized in that: The composite positive electrode material is used to prepare the positive electrode of a lithium ion battery.
10. A lithium battery, characterized in that: The positive electrode of the lithium-ion battery is the composite positive electrode material according to any one of claims 1 to 4, and the negative electrode is a carbon silicon material.
Citation Information
Patent Citations
Composite coated lithium ion battery positive electrode material and preparation method thereof
CN113471415A
Positive electrode lithium supplement agent and preparation method and application thereof
CN114530634A
Lithium supplement agent for positive electrode material of lithium battery and preparation method of lithium supplement agent
CN115275200A
Positive electrode composite material and preparation method thereof, positive plate and secondary battery
CN115295771A
Composite positive electrode material and preparation method thereof, positive plate and secondary battery
CN117117181A
Cited By
A positive electrode slurry, a positive electrode sheet, and a preparation method and application thereof
CN122950373A